Pelatihan OSN Matematika Melalui Soal Berbasis Critical Thinking Skill Bagi Siswa SMP Negeri 4 Tanjungpinang - Mariyanti Elvi; Metta Liana; Dios Sarkity; Dina Fitriyah (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2020)
he National Science Olympiad (OSN) is one of the government's strategies to improve the quality of education in Indonesia. The purpose of OSN is to develop critical, systematic, creative, innovative and productive thinking skills. Critical thinking skills is a present skill that must be developed by students. The results of the OSN which is not optimal, one of which is caused by not optimal preparation by the school in dealing with OSN selection. The purpose of this activity is to equip students of SMP Negeri 4 Tanjungpinang so they are ready Mathematics Olimpiade selection by giving questions based on critical thinking skills. The results of this activity are (1) students are very competitive and enthusiastic in participating in training, (2) students arealso motivated to participate in OSN 2020 selection, (3) the application of critical thinking skills makes it easier for students to analyze questions and solve them